ANALISIS HUBUNGAN MODAL SOSIAL DAN TINGKAT PENDAPATAN AGROFORESTRI PETANI KELOMPOK HUTAN KEMASYARAKATAN DI KPHL BATU TEGI - Adella Putri Apriliani; Hari Kaskoyo; Samsul Bakrie (Journal of People, Forest and Environment, 2022)
Social capital can improve people's welfare and community productivity as it is based on trust, norms, and social networks. Social capital is also influenced by community participation in sustainable forest management, one form of community participation can be in the form of agroforestry management. This study aims to determine the effect of social capital in increasing the income of agroforestry communities managing HKm in the Batutegi Forest Management Unit (KPH) area. Cluster Random Sampling in HKm KPHL Batu Tegi has 15 Gapoktan including Gapoktan Wanatani Lestari, Gapoktan Mahardika, and Gapoktan Hijau Makmur. In this study, the number of samples used for each gapoktan was 50 respondents so that the total number of respondents from the three gapoktans was 150 respondents. The results showed that there was no significant effect of trust performance on earnings. This shows that in HKm the higher/lower the trust between farmers, the higher/lower the influence of social capital on income will be. A significant influence can be seen from the performance of social networks on income. This shows that the influence of the performance of the social network has a positive direction, and it means that the higher the level of the social network, the higher the income of the community.